Fandom affiliation and tribal behaviour: A sports marketing application - Dionísio, P.; Leal, C.; Moutinho, L. (Qualitative Market Research: An International Journal, 2008)
Purpose - The aim of this paper is to identify the existence of tribal behaviour in football fans and the impact of this tribalism on the consumption of brands associated with the club. The intention is not to recognize tribal relationships between fans and their club but to identify to what extent the fan commitment level can impact the preference for sponsor brands. Design/methodology/approach - Two focus groups were made with two distinct types of club supporters, namely the members of one supportive organized group and another with highly-devoted fans. Findings - Research questions posed in this study were mostly confirmed: football-devoted supporters have a kind of cult with their club and it is possible to distinguish several distinct fan typologies varying with the level of fan commitment. The associative behaviour of football fans is influenced by affiliation through the need for social recognition, socialization and symbolism. The study also reveals that devoted fans assume an effective knowledge of club association with some brands but they do not manifest an effective preference towards them. Research limitations/implications - The main limitation refers to the restricted research scope, i.e. one country, one club and one supporting associative group. Practical implications - Managerial implications are related to the club needing to maintain an open channel with supporters. Sponsor brands should also develop a long-term strategy and support another sport besides football. Originality/value - This paper provides exploratory research in an area of great popularity, relating tribal behaviours with brand strategies which involve millions of euros all over the world.